'Bacterial Programmed Cell Death': cellular altruism or genetic selfism?. Issue 16 (21st August 2020) - Ramisetty, Bhaskar Chandra Mohan; Sudhakari, Pavithra Anantharaman
ABSTRACT: Cell-dependent propagation of the 'self' is the driver of all species, organisms and even genes. Conceivably, elimination of these entities is caused by cellular death. Then, how can genes that cause the death of the same cell evolve? Programmed cell death (PCD) is the gene-dependent self-inflicted death. In multicellular organisms, PCD of a cell confers fitness to the surviving rest of the organism, which thereby allows the selection of genes responsible for PCD. However, PCD in free-living bacteria is intriguing; the death of the cell is the death of the organism. How can such PCD genes be selected in unicellular organisms? The bacterial PCD in a population is proposed to confer fitness to the surviving kin in the form of sporulation, nutrition, infection-containment and matrix materials. While the cell-centred view leading to propositions of 'altruism' is enticing, the gene-centred view of 'selfism' is neglected. In this opinion piece, we reconceptualize the PCD propositions as genetic selfism (death due to loss/mutation of selfish genes) rather than cellular altruism (death for the conferment of fitness to kin). Within the scope and the available evidence, we opine that some of the PCD-like observations in bacteria seem to be the manifestation of genetic selfism by Restriction–Modification systems and Toxin–Antitoxin systems. Abstract : Genetic selfism of selfish DNA begets cellular death in bacteria.